2021
DOI: 10.1111/ddi.13448
|View full text |Cite
|
Sign up to set email alerts
|

Life history strategies differentiate established from failed non‐native freshwater fish in peninsular Florida

Abstract: Aim Non‐native fishes threaten native biodiversity worldwide. Life history traits have been used to predict the risk of establishment for non‐native fish in several regions of the world and parts of the United States, but not yet for Florida despite the elevated risk of establishment in the state due to many invasion pathways and favourable climate. Our goal was to identify which life history traits may be useful for predicting which non‐native freshwater fishes might successfully establish populations in Peni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 70 publications
2
10
0
Order By: Relevance
“…This behaviour has been positively selected in the ornamental industry and is thus more represented among introduced species worldwide. This result corroborates the findings of previous studies at more local scales, which observed a higher establishment success for exotic fish with a high level of parental care (Lawson & Hill, 2022; Marchetti et al, 2004), although they were unable to demonstrate a specific link between the location of establishment and parental care. For terrestrial vertebrates, parental care is often associated with slow life history.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This behaviour has been positively selected in the ornamental industry and is thus more represented among introduced species worldwide. This result corroborates the findings of previous studies at more local scales, which observed a higher establishment success for exotic fish with a high level of parental care (Lawson & Hill, 2022; Marchetti et al, 2004), although they were unable to demonstrate a specific link between the location of establishment and parental care. For terrestrial vertebrates, parental care is often associated with slow life history.…”
Section: Discussionsupporting
confidence: 92%
“…This behaviour has been positively selected in the ornamental industry and is thus more represented among introduced species worldwide. This result corroborates the findings of previous studies at more local scales, which observed a higher establishment success for exotic fish with a high level of parental care (Lawson & Hill, 2022;Marchetti et al, 2004), although they were unable to F I G U R E 4 Trait comparison between the four groups of fish. The four groups correspond to the establishment levels: species introduced inside their native bioregion in four basins or less (In < 4), inside their native bioregion in more than four basins (In > 4), outside their native bioregion in four basins or less (Out < 4) and outside their native bioregion in more than four basins (Out > 4).…”
Section: Importance Of Traits To Disentangle the Dimensions Of Establ...supporting
confidence: 91%
See 1 more Smart Citation
“…Specifically, studies considering morphological differences between natives and non-natives at the river basin scale showed that non-native species had larger size and less elongated bodies than the native counterparts 9 , 28 , 29 . Furthermore, growing evidence suggests non-native species have different traits than native species within river basins 5 , 10 , 11 , 30 . Our regional (watershed) approach over the continental US revealed that functional traits, including morphological, physiological, and life-historical aspects differ between native and non-native species (including translocated and exotic species), therefore paralleling previous studies at both local and global scales.…”
Section: Discussionmentioning
confidence: 99%
“…From 2010 onward, we observed markedly different responses to the disruption in species in the three different zones. Compared to highly migratory pelagic species (such as mackerel and tuna) that have high growth and reproductive rates, demersal fish are mostly sedentary K-selection species and exhibit slow growth, a long lifespan, and a low reproductive rate [ 67 ], which may be even more disadvantageous in extreme climates.…”
Section: Discussionmentioning
confidence: 99%